The Influence of Regional Minimum Wage Levels and Unemployment on Poverty Levels in North Sumatra Province - Nur Aulia Pratiwi; Empi Aura Kania; Laili Hasmiyah Harahap (Outline Publisher, 2026)
Purpose: This study examines the effects of the Regional Minimum Wage (UMR) and unemployment on the poverty rate in North Sumatra, both partially and simultaneously. Methods: A quantitative approach was employed using secondary data obtained from the Central Bureau of Statistics (BPS) of North Sumatra Province. Data were analyzed using multiple linear regression with the Ordinary Least Squares (OLS) method. Classical assumption tests—normality, multicollinearity, heteroskedasticity, and autocorrelation—were conducted to ensure model validity. Results: The results indicate that the regression model meets all classical assumptions. The multiple regression analysis shows that the Regional Minimum Wage (UMR) significantly affects the poverty rate in North Sumatra (p < 0.05). Unemployment also has a significant effect on poverty levels (p < 0.05). Simultaneously, UMR and unemployment significantly influence the poverty rate (p < 0.05). The coefficient of determination reveals that both variables explain 82.38% of the variation in the poverty rate. Conclusions: The study concludes that wage levels and unemployment are key determinants of poverty in North Sumatra. Therefore, labor market policies and minimum wage regulations play an important role in poverty reduction. Originality/value: This study provides region-specific empirical evidence on the relationship between minimum wage, unemployment, and poverty in North Sumatra, offering valuable insights for policymakers in formulating targeted poverty alleviation strategies.